2016
DOI: 10.7717/peerj.2196
|View full text |Cite
|
Sign up to set email alerts
|

Tissue mortality by Caribbean ciliate infection and white band disease in three reef-building coral species

Abstract: Caribbean ciliate infection (CCI) and white band disease (WBD) are diseases that affect a multitude of coral hosts and are associated with rapid rates of tissue losses, thus contributing to declining coral cover in Caribbean reefs. In this study we compared tissue mortality rates associated to CCI in three species of corals with different growth forms: Orbicella faveolata (massive-boulder), O. annularis (massive-columnar) and Acropora cervicornis (branching). We also compared mortality rates in colonies of A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…ciliates) noted here in corals with SCTLD are likely incidental following skeletal exposure. Ciliates have been associated with TLD lesions in the Pacific (Work et al, 2012) and in the Caribbean (Verde et al, 2016). Of particular interest are the trichodinid ciliates not reported previously in corals and the epidermal apicomplexans.…”
Section: Discussionmentioning
confidence: 89%
“…ciliates) noted here in corals with SCTLD are likely incidental following skeletal exposure. Ciliates have been associated with TLD lesions in the Pacific (Work et al, 2012) and in the Caribbean (Verde et al, 2016). Of particular interest are the trichodinid ciliates not reported previously in corals and the epidermal apicomplexans.…”
Section: Discussionmentioning
confidence: 89%
“…These organisms were recorded in nine different diseases ( Sweet & Séré, 2016 ) and particularly, they have been reported in cases of WS in species from the Indo Pacific ( Sweet & Bythell, 2015 ), Central Pacific ( Work, Russell & Aeby, 2012 ), and the Caribbean ( Croquer et al, 2016 ). Ciliates have been described as the agent involved in the pathogenesis of diseases due to its ability to consume the coral tissue in the lesion’s interface ( Verde, Bastidas & Croquer, 2016 ), but also as secondary pathogens after initial bacterial infection ( Sweet & Bythell, 2015 ). In any case, their presence at the margin of diseased tissues would make the repair of the epithelium more difficult ( Work, Russell & Aeby, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…White band disease is a common coral disease observed at high temperatures throughout the Pacific Ocean and the Arabian Gulf and is manifested with tissue loss at the lesion site that exposes the coral skeleton 21 (Supplementary Figure 3 ). White band disease causes rapid tissue loss during the hot summer months in the Arabian Gulf in both Acropora and Platygyra 3 , spreading a few millimeters daily 23 . Although infected corals in this study exhibited tissue loss characteristic of this disease, we have not confirmed this and thus refer to these colonies as suffering from a white syndrome disease.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cyanobacteria that dominate the microbiome of corals infected with black band disease produce quorum sensing inhibitors that may disrupt communication between members of the indigenous microbiome 22 , leading to a potential disruption of a stable coral microbiome and weakening of the holobiont system. On the other hand, white band disease, a type of white syndrome diseases, though widely investigated to have rapid disease progression 23 and high infection rates in corals under stress 24 , 25 , has an unclear cause of infection.…”
Section: Introductionmentioning
confidence: 99%